Recombinant Zoster Vaccine (Shingrix): a nex gun for Rheumatologist - D. Marotto; P. Sarzi Puttini; A. Riva (Verduci Editore, 2022)
Herpes Zoster, or as commonly known shingles, is a debilitating painful rash occurring at any age in anyone caused by reactivation of the varicella zoster virus (VZV). The lifetime risk of HZ in the general population is around 30% HZ incidence increases with age and is estimated that 90% of adults have contracted VZV and are therefore at risk of developing HZ and that at least 1 in 3 individuals will develop the disease in their lifetime. Increased HZ incidence, attributed to a decline in immunity, is observed in elderly people and in patients using immunosuppressive medications. In light of the significant burden caused by HZ and its complications in frail patients, adopting a preventive strategy seems promising, particularly using vaccination in appropriate age and risk groups.